2017
DOI: 10.1016/j.ijsu.2017.03.031
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of combined intravenous and topical administration of tranexamic acid with intravenous tranexamic acid alone for blood loss reduction after total hip arthroplasty: A meta-analysis

Abstract: Our meta-analysis suggests that the combined application of IV and topical TXA for patients undergoing THA may reduce the total blood loss compared with IV use alone without increasing the risk of postoperative complications. However, due to the quality and number of included studies, more studies were need to further identify the optimal dose for combine IV-TXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
0
27
0
5
Order By: Relevance
“…However, they established that there was a difference in the amount of TXA between the topical (2 g) and IV (1 g) groups. Liu et al [50] in their meta-analysis study in patients after THA reported that the combined application of IV and topical TXA reduced the total blood loss compared with IV use alone. Moreover, they did not report an increased risk of complications.…”
Section: Comparison Between Local and IV Applicationmentioning
confidence: 99%
“…However, they established that there was a difference in the amount of TXA between the topical (2 g) and IV (1 g) groups. Liu et al [50] in their meta-analysis study in patients after THA reported that the combined application of IV and topical TXA reduced the total blood loss compared with IV use alone. Moreover, they did not report an increased risk of complications.…”
Section: Comparison Between Local and IV Applicationmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a synthetic antifibrinolytic agent that has been routinely administered in many surgical fields. [ 6 , 7 ] TXA has been used in TSA since 2015, and the efficacy of TXA in TSA has been debated. Friedman et al [ 8 ] determined that TXA could decrease the need for transfusion in TSA patients, while Gillespie et al [ 9 ] found that there was no significant difference between TXA and controls in terms of the need for transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the combined method of TXA has been widely used in TKA and THA. Current studies have confirmed that the combined regimen of intravenous infusion of TXA combined with intra‐articular local injection is superior to the single‐route regimen. Through a prospective study of 150 patients, Huang et al found that the combined regimen of TXA in TKA could reduce the overall effect of perioperative bleeding and even replace the role of the tourniquet.…”
Section: Discussionmentioning
confidence: 99%